The potential of the organic micropollutants emission from swimming accessories into pool water - Anna Lempart; E. Kudlek; M. Dudziak (Environment International, 2020)
The potential leaching of organic micropollutants from swimming accessories was studied in the laboratory experiment. Seventeen different swimming accessories have been placed in various water matrices under different conditions in order to reproduce the actual environmental conditions of swimming pool water. The presence of micropollutants in water samples, after the exposure of swimming accessories, was assessed using indirect indicators (Total Organic Carbon and Phenol Index) and directly using a gas chromatograph coupled with a mass spectrometer with electron ionization. A wide range of organic compounds emitted from swimming accessories have been identified. The most common in tested samples was isophorone. The frequency of its occurrence in 50 swimming pools located in Poland was equal to 89% in concentrations ranged from 0.75 to 1.01 µg L−1 (below the concentration of 40 µg L−1, which is estimated to increase the cancer risk). Content of combined chlorine (1.52–3.16 mgCl2 L−1) in chlorinated matrices indicated a high potential for disinfection by products (DBPs) formation from organic matter emitted into pool water from swimming accessories. Ten of seventeen tested samples showed the toxic effect, measured as the bioluminescence inhibition of bacteria Aliivibrio fischeri. Keywords: Micropollutants, Swimming pools, DBPs precursors, Industrial additives